CANDAS Dataset: A Cooling Fan Sound Dataset with Modeled Disturbances and Controlled Experimental Conditions - Lima, Henrique; Silva, Cristofer; Nery, Ricardo; Camacho, Wilmer Córdoba; Brazileiro, Ricardo; Monteiro, Rodrigo de Paula; Ribeiro, Andrea Maria Nogueira Cavalcanti; Bastos-Filho, Carmelo José Albanez; Cerrada, Mariela; Pinheiro, Diego (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2025)
Predictive maintenance cuts economic and safety risks in rotating machinery by leveraging vibration and acoustic data, which machine-learning models convert into intelligent fault detectors. Acoustic signals are especially powerful for early fault detection and cooling fans, with simple rotational dynamics, are convenient proxies for complex rotors. Yet existing fan datasets lack disturbance models and controlled conditions. We present CANDAS, a controlled sound dataset featuring 28 h of recordings from two cooling fans under five modeled disturbance conditions. Baseline experiments with three anomalydetection models validate its value, advancing reproducible research on acoustic fault detection in rotating machinery.